Long-Term Application of Cerebellar Transcranial Direct Current Stimulation Does Not Improve Motor Learning in Parkinson’s Disease - de Albuquerque, Lidio Lima; Pantovic, Milan; Clingo, Mitchell G.; Fischer, Katherine M.; Jalene, Sharon; Landers, Merrill R.; Mari, Zoltan; Poston, Brach (Cerebellum (London, England), 2022)
Cerebellar transcranial direct current stimulation (c-tDCS) enhances motor skill acquisition and motor learning in young and old adults. Since the cerebellum is involved in the pathophysiology of Parkinson’s disease (PD), c-tDCS may represent an intervention with potential to improve motor learning in PD. The primary purpose was to determine the influence of long-term application of c-tDCS on motor learning in PD. The secondary purpose was to examine the influence of long-term application of c-tDCS on transfer of motor learning in PD. The study was a randomized, double-blind, SHAM-controlled, between-subjects design. Twenty-one participants with PD were allocated to either a tDCS group or a SHAM stimulation group. Participants completed 9 practice sessions over a 2-week period that involved extensive practice of an isometric pinch grip task (PGT) and a rapid arm movement task (AMT). These practice tasks were performed over a 25-min period concurrent with either anodal c-tDCS or SHAM stimulation. A set of transfer tasks that included clinical rating scales, manual dexterity tests, and lower extremity assessments were quantified in Test sessions at Baseline, 1, 14, and 28 days after the end of practice (EOP). There were no significant differences between the c-tDCS and SHAM groups as indicated by performance changes in the practice and transfer tasks from Baseline to the 3 EOP Tests. The findings indicate that long-term application of c-tDCS does not improve motor learning or transfer of motor learning to a greater extent than practice alone in PD.